Giving quality lives to our families, enhancing government's performance: A woman's perspectives on the cultural dimension of development - Sackey, B.M. (Jenda, 2004)
This study focuses on one woman and her quest for development using her familiar cultural approach of reciprocity. In this way, she could effectively make positive changes in her own socio-economic status, as well as that of her family and the wider community. Indeed, she was also able to have the name of her country imprinted on the map of the global fishing industry. This case study is predicated on the premise that the nurturing of good social relations leads to community and national development. It observes that if government should adopt the cultural reciprocity approach, that will form a basis for mutual good relationship with its citizens, and give women incentives and stimulation in their work, it will in turn enhance its own performance. © Africa Resource Center, Inc. Publisher, 2004.